PENGARUH SUBSTITUSI TEPUNG LARVA BLACK SOLDIER FLY PADA TEPUNG BUNGKIL KEDELAI TERHADAP KELUARAN KREATININ KELINCI NEW ZEALAND WHITE - Nur Azzimahtul Zahroh; S Sutaryo; Sri Lestari; Agung Purnomoadi (MEDIAGRO, 2020)
Soybean meal is a source of protein that is commonly used for animal feed, however, the availability of soybean meal in Indonesia is still dependent on import so it is necessary to find the feed alternative for substitution of soybean meal. The purpose of the research was to evaluate the effect of black soldier fly (BSF) larvae meal for protein source to substitutesoybean meal on New Zealand White rabbit through the excreted ofcreatinine. The research was carried out usinga completely randomized design (CRD) with 4 treatments and 4 replications. The treatments werea complete feed with 100% soybean meal(T0), acomplete feed with 90% soybean meal + 10% BSFmeal (T1), acomplete feed with 80% soybean meal + 20% BSFmeal(T2), acomplete feed with 70% soybean meal + 30% BSFmeal (T3). The results showed that there was no effect of the BSF mealon the energy comsumption with an average 273.50 kcal/day and creatinine excretion (P> 0.05) with an average of 16.80mg/day atthe 6th week and 22.54 mg/day at the 10th week. Therefore, it can be concluded that theBSF larvae can replace soybean meal in the ration without negative effect on metabolismprotein rate of NZW rabbit. Keywords: Rabbit, soybean meal, Black soldier Fly, Energy comsumption, Creatinine output.